Spinal Epidural Abscess: Common Symptoms of an Emergency Condition: A Case Report. Issue 4 (August 2013) - Rosc-Bereza, K.; Arkuszewski, M.; Ciach-Wysocka, E.; Boczarska-Jedynak, M.
Spinal epidural abscess (SEA) is a severe pyogenic infection of the epidural space that leads to devastating neurological deficits and may be fatal. SEA is usually located in the thoracic and lumbar parts of the vertebral column and injures the spine by direct compression or local ischemia. Spinal injury may be prevented if surgical and medical interventions are implemented early. The diagnosis is difficult, because clinical symptoms are not specific and can mimic many benign conditions. The classical triad of symptoms includes back pain, fever and neurological deterioration. The gold standard in the diagnostic evaluation is magnetic resonance imaging with gadolinium enhancement, which determines the location and extent of the abscess. Increased awareness of the disease is essential for rapid recognition and immediate implementation of treatment. Here we describe the case of a 26-year-old woman with SEA with fever, back pain in the thoracic region and delayed symptoms of a transverse spinal cord injury.